Ekiti Parapo War: A Historical Trajectory - Familugba, Jonathan Oluropo (Journal of Historical Studies, 2024)
Purpose: The purpose of this study is to examine the historical factors that led to the war between the Ekiti and the Ibadan people who are all of Yoruba extraction in Southwestern Nigeria. The paper discusses the course and the process through which the war was fought; it also brought out the consequences of the war as it affects the Ekiti People and the entire people of southwestern Nigeria. Methodology: Being a historical study, the research methodology adopted was that of historical enquiry into the past. Primary sources of data consulted included archival materials such as correspondences, minutes of meeting and annual report of colonial government. While secondary data were sourced from theses, journal articles, books and other publications from the internet. Findings: The study revealed that it was the war that solidified the cultural unity and homogeneity of Ekiti people of Southwestern Nigeria. In fact, Olomola had described this period as "the most celebrated instance of the application of "˜ethnic' solidarity among Ekiti communities."[1] Unique Contribution to Theory, Policy and Practice: Knowledge acquired from this study would be able to make readers gain specific knowledge on the factors that led to the war between the Ekiti and the Ibadan imperialists who are both of Yoruba extraction of Southwestern Nigeria in the 19th Century. One unique point included in this study was the resilience and doggedness with which the Ekiti and her allies fought and sustained the tempo of the liberation war for the long period it lasted before the British intervention finally brought the war to a conclusive end. Therefore, peace advocates, policy makers, governments both at the national and international levels should draw from the collective memories of the war to strengthen cultural identity and rejig national consciousness in building a better and more formidable nation.